Role of Finance in Dixit-Stiglitz-Krugman Model of International Trade - Sugata Marjit; Meghna Dutta; Moushakhi Roy (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper introduces finance or credit in the Dixit-Stiglitz-Krugman (DSK) model of international trade. It identifies mechanisms by which finance can affect the main results of the conventional model. The key results are as follows. Perfect credit market does not affect number of varieties or output per variety, but it affects wage and interest rate, thus affecting income distribution. With a minimum wage and unemployment availability of credit affects number of varieties. With imperfect credit market, wealthier firms face lower cost of credit and produce greater number of varieties and given labour force less output per variety. Thus, availability of finance will determine a specific trade pattern between richer and poorer nations both with unemployment and imperfect credit market , a result in stark contrast with the conventional model with indeterminate pattern of trade.
Keywords: F16; F20; J31; 330; product variety; factor mobility; unemployment; finance; trade